NEW DIMENSIONS OF ENTREPRENEURSHIP IN TERMS OF INTELLECTUAL PROPERTY POLICY IN INDIA - Dr. Pooja Aggarwal (Galaxy International Interdisciplinary Research Journal, 2021)
Intellectual property rights cover the development of human intelligence as well as the right to protect and manage that investment portfolio. Intellectual property rights, like any other type of property right, are intangible. Intellectual Property Rights usually provide the inventor exclusive rights to utilize his or her innovation for a certain period of time. Intellectual Property Rights have become one of the primary wealth drivers in the current era, particularly in the context of entrepreneurial behavior, as a result of the rapid expansion in globalization and the opening up of new fields in India.Intellectual property rights now pervade almost every facet of modern life. IPRs serve a critical role in ensuring the country’s long-term development. Every start-up has intellectual property rights that it must understand and protect to succeed. IP policy is one of the most significant policies for R&D management to improve research and innovation. The goal of this study paper is to look into India’s multiple intellectual property rights. This planned study also sheds light on the different problems that come with raising broad knowledge about intellectual property rights. The main objective of this research study was to highlight how intellectual property rights are evolving in today’s society. Finally, the study paper will make recommendations for how to deal with intellectual property rights in the context of entrepreneurship.